Extracellular Vesicles From KSHV-Infected Cells Stimulate Antiviral Immune Response Through Mitochondrial DNA - Jeon, Hyungtaek; Lee, Jisu; Lee, Suhyuk; Kang, Su-Kyung; Park, Sang June; Yoo, Seung-Min; Lee, Myung-Shin (Frontiers in Immunology, 2019)
Kaposi’s Sarcoma-associated herpesvirus (KSHV) is the etiologic agent of Kaposi’s sarcoma, which is the most common cancer in acquired immune deficiency syndrome patients. KSHV contains a variety of immunoregulatory proteins. There have been many studies on the modulation of antiviral response by these immunoregulatory proteins of KSHV. However, the antiviral effects of extracellular vesicles (EVs) during de novo KSHV infection have not been investigated to our best knowledge. In this study, we showed that KSHV-infected cells induce interferon-stimulated genes (ISG) response but not type I interferon in uninfected bystander cells using EVs. mRNA microarray analysis showed that ISGs and IRF-activating genes were prominently activated in EVs from KSHV-infected cells (KSHV EVs)-treated human endothelial cells, which were validated by RT-qPCR and western blot analysis. We also found that this response was not associated with cell death or apoptosis by virus infection. Mechanistically, the cGAS-STING pathway was linked with these KSHV EVs-mediated ISGs expressions, and mitochondrial DNA on the surface of KSHV EVs was one of the causative factors. Besides, KSHV EVs-treated cells showed lower infectivity for KSHV and viral replication activity than mock EVs-treated cells. Our results indicate that EVs from KSHV-infected cells could be an initiating factor for the innate immune response against viral infection, which may be critical to understanding the microenvironment of virus-infected cells.